Demonstrating microdroplet coalescence for tailored and biodegradable microgel fabrication1. Issue 70 (31st July 2015) - Simone, G.
<x xml:space="preserve">Abstract</x> Coalescence of microdroplets, mimicking Nature, has been exploited to form gelatin microparticles. The microgels are biodegradable and biocompatible.